Structural capacity reduction of drilled shaft foundations due to corrosion in longitudinal bars - Abi Shdid, Caesar (2014)
Drilled shafts are a common type of deep foundations used to support a wide array of infrastructure facilities such as bridges, high mast lighting, tanks and communication towers. The deep inaccessible subterranean nature and the construction procedures of drilled shafts result in various types of anomalies; most critical of which being necking and voids. This necking or voids translates to loss of concrete cover around the longitudinal bars and its subsequent exposure to the surrounding soil, leading to corrosion. An experimental study using large-scale drilled shaft samples is presented that evaluates the effect of different percentages of rebar corrosion on the axial load capacity of drilled shaft foundations. Results show that the presence of corrosion in the longitudinal bars affects both the strength and buckling capacity of a shaft, and that a 25% necking or void area will result in more than 60% of axial capacity loss of the shaft over a time period of 20 years.